Financial performance analysis using economic valued added method on the sub sector of cigarette listed on the Indonesia Stock Exchange - Arien Agustin; Febrianty Febrianty (Jurnal Ekonomi LLDIKTI Wilayah 1 (JUKET), 2022)
This study aims to determine the financial performance using the Economic Value Added method in the cigarette sub-sector listed on the Indonesia Stock Exchange for the last five years. The research method used is a quantitative method with a descriptive approach. The data used is secondary data in the form of Company Financial Statements obtained from the official website of the Indonesia Stock Exchange. The results of the study are based on an analysis using the EVA method from five food and beverage companies that have good financial performance (positive EVA) during the 2016-2020 period, namely, GGRM and WIIM. Analysis of the company's performance with the method shows the EVA fluctuating results. This is because the value of NOPAT and capital charges is very influential on EVA results. Where if the NOPAT value is greater than the value of capital charges, the resulting EVA will increase and vice versa.